Some Research Results from the Application of Geophysical Methods in Quickly Identifying Shallow Hazards in Dike and Dam Body - Minh, Vũ Đức; Chung, Đỗ Anh (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 1, 2013)
Abstract : Small and shallow caves are frequently found on the dike and dam system inside our country, leading to some risks of subsidence, seepage, even dyke and dam rupture. The handling of this problem is relatively simple if we can accurately identify the location of these hollow caves. The question is how to study and find out the geophysical method to quickly and accurately determine the location and size of these caves for timely treatment in order to improve the efficiency of the survey. This paper presents some new results obtained when studying and applying the Improved multi-electrode (2D and 3D) and Ground penetrating radar methods to rapidly determine the hollow caves at K112+697 position of the Red River right dam in Hà Nội and at K21+900  position of Dao River left dam in Nam Định. The paper also assesses the capability and effectiveness of each method in the determination of this object. Keywords: Hollow cave, termite, sinkhole, Improved multi-electrode, Ground penetrating radar.